The Calgary student run clinic in context: a mixed-methods case study (Canadian Medical Education Journal, 2019)
Background: Student Run Clinics (SRCs) provide students with clinical education while caring for underserved populations. While much of the research on SRCs comes from the USA, SRCs in other contexts need to be appraised in the context of the systems they interact with. This study explored how stakeholders in the University of Calgary’s SRC perceived its purpose and beneficiaries with respect to patients, students, undergraduate medical education, and its intersections within the healthcare system in Calgary. Methods: Data came from the SRC’s EMR and stakeholder interviews at the Inn from the Cold (IFTC) shelter. Qualitative data were analyzed using standard grounded theory techniques.Results: There were 13 interviews - seven with student clinicians and six with preceptors and other stakeholders. Interviews highlighted the uncertainty of the SRCs role. Majority of participants saw the SRC as facilitating further access to other healthcare services, while some commented on its primarily education-focused role. Major limitations in the SRC’s scope of care and its integration with other services were identified.Conclusion: SRCs need to consider theiraccountabilities, both educational and healthcare-focused at individual and organization levels, in order to function as responsible healthcare providers in Calgary.